The fire by night : a novel - Messineo, Teresa (New York, NY : William Morrow, 2017)
A novel commemorating the unsung heroines of World War II traces the experiences of two military nurses who fight for survival and care for others in a makeshift medical unit and a POW camp, enduring dangerous existences while waiting for the war to end.
Keywords: Nurses -- Fiction; World War, 1939-1945 -- Women -- Fiction; World War, 1939-1945 -- Fiction; Nurses -- Fiction; World War, 1939-1945 -- Women -- Fiction; World War, 1939-1945 -- Fiction; Historical fiction; Historical fiction